Synthesis and application of dual functionalized task specific ionic liquid for bamboo dissolution - Sultan, N.S.H. (EDP Sciences, 2017)
A new class of dual functionalized imidazolium based ionic liquid (IL) namely 3-(2-cyano-ethyl)-1-(2-ethoxy-ethyl)-3-imidazolium bromide CNEIMBr, was synthesized and characterized to study their potential in bamboo dissolution. The chemical structure for the IL was characterized using NMR (1H and 13C). Thermal properties, surface morphology and functional group of the native bamboo and IL treated bamboo were analyzed by Thermal Gravimetric Anaylysis (TGA), Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR) respectively. The new IL was able to dissolve up to 5wt% of bamboo biomass within 48 hours and 100°C. © The Authors, published by EDP Sciences, 2017.